Aspek Ketatanegaraan Pengadaan Tanah Pembangunan Jalan Tol Semarang-Demak dalam Perspektif Hak Warga Negara - Shofi, Siti Shofiah (Jurnal Ragam Pengabdian, 2026)
Land acquisition for the construction of the Semarang–Demak Toll Road is one of the national strategic projects that carries complex constitutional dimensions. This project not only involves legal mechanisms for land acquisition, but also directly concerns the constitutional rights of citizens as guaranteed by the 1945 Constitution of the Republic of Indonesia. This article aims to analyze the constitutional aspects of land acquisition in the development of the Semarang–Demak Toll Road and to examine its conformity with the principle of protecting citizens’ rights within the framework of a rule-of-law state. This study employs a normative legal research method with a descriptive-analytical approach through literature review of laws and regulations, policy documents, and relevant legal literature. The results of the study indicate that although the land acquisition mechanism has formally referred to Law Number 2 of 2012 and its implementing regulations, there remain several constitutional issues that require attention, including: the tension between the principle of public interest and citizens’ land rights, the effectiveness of mechanisms for fair and proper compensation, and citizens’ accessibility to objection procedures and justice. In particular, the uniqueness of this project as integrated infrastructure that also functions as a sea embankment adds complexity to its impact on citizens’ rights, especially for coastal communities. This article concludes that it is necessary to strengthen mechanisms for protecting citizens’ constitutional rights at every stage of land acquisition in order to achieve a balance between national development and the guarantee of human rights.